(3TQM CQLhRI aj eKdKGJ bWQHs - (3eLghds; (3CHj Ydj Hf CMeO Hf GdeSJfjQ, bWQH,J (B206 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYXje GdHGQF hNGdb GdCSeGY hGdCHUGQ hHYO JSdjei Ydi cd fHi CTQM ai eKdKGJ bWQH CQLhRI SGFZI ai GdeTQH JQhb ai eSGeY GdMVGQ s
(3BNQgG (B:s
(3Ke GdVjGY hGdHdGO aGdbQi eYQhbI ef ZjQ Pi EfcGQ Ke GdUdGI hGdSdGe SQeOkG Ydi GdfHi GdgGTei CMeOG hBdg GdZQ hUMHg eDHOkG ef YfO QH efYe ZaGQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B_ (3GdeZQH (B(190) s
Keywords: (3GdeLGejYs